Functional Characterization of the Canine Heme-Regulated eIF2α Kinase: Regulation of Protein Synthesis - Kimon C. Kanelakis; Jayashree Pyati; Pamela C. Wagaman; Jui Chang Chuang; Young Yang; Nigel P. Shankley (Advances in Hematology)
The heme-regulated inhibitor (HRI) negatively regulates protein synthesis by phosphorylating eukaryotic initiation factor-2α (eIF2α) thereby inhibiting protein translation. The importance of HRI in regulating hemoglobin synthesis in erythroid cells makes it an attractive molecular target in need of further characterization. In this work, we have cloned and expressed the canine form of the HRI kinase. The canine nucleotide sequence has 86%, 82%, and 81% identity to the human, mouse, and rat HRI, respectively. It was noted that an isoleucine residue in the ATP binding site of human, rat, and mouse HRI is replaced by a valine in the canine kinase. The expression of canine HRI protein by in vitro translation using wheat germ lysate or in Sf9 cells using a baculovirus expression system was increased by the addition of hemin. Following purification, the canine protein was found to be 72 kD and showed kinase activity determined by its ability to phosphorylate a synthetic peptide substrate. Quercetin, a kinase inhibitor known to inhibit mouse and human HRI, inhibits canine HRI in a concentration-dependent manner. Additionally, quercetin is able to increase de novo protein synthesis in canine reticulocytes. We conclude that the canine is a suitable model species for studying the role of HRI in erythropoiesis.